MANAGEMENT OF PERSONALIZED LEARNING STRATEGIES AS CORRELATES OF ACADEMIC PERFORMANCE OF NCE STUDENTS IN STATE COLLEGES OF EDUCATION IN SOUTH EAST, NIGERIA (Scientific Journal of Educational Management, Research and law, 2026)
The study management of personalized learning strategies as correlate of academic performance of NCE students in state colleges of education in South east, Nigeria. The study adopted a correlational survey design. The population of this study was531 second year NCE students from state owned Colleges of Education in South East, Nigeria comprised of 65 students from Abia State College of Education, Technical Arochukwu, 105 students from Ebonyi State College of Education, Ikwo, 120 students from Enugu State College of Education Technical, 89 students from Imo State College of Education, IhitteUboma and 152 students from Nwafor Orizu College of Education, Anambra. The sample size for the study was 531 BCE students thus there was no sampling techniques since the population of the study was manageable and controllable by the researchers. The instrument for data collection was the researchers’ development questionnaires titled Management of Personalized Learning Strategy Questionnaire (MPLSQ) and Academic Performance Questionnaire (APQ). MPLSQ and APQ were validated by three experts; two from school of education and one from school of business education, Abia State College of Education, Technical. Cronbach Alpha method was used to determine the internal consistency of MPLSQ and APQ which yielded a reliability alpha of .91 and .88 for respectively. five briefed research assistants helped in the administration and collection of the questionnaires. Data collected from the field were analysed using Pearson Product Moment Correlation Coefficient (PPMCC) to answer the research questions while Linear regression was used to test the null hypotheses that guided the study at 0.05 level of significance. Based on the analysis of the study, the following findings were made; that using of emerging learning technologies to a significant positive moderate extent relates to academic performance; that project-based learning has a significant positive moderate extent with academic performance. From the findings of the study, the researcher recommended amongst other that; Government in collaboration with college of education management should set up e-learning classroom to encourage the students in using emerging learning technologies for their academic purposes so as to meet with the students academic diverse need.